Exploring M-Learning User Information Systems through the Development of a Comprehensive Technology Acceptance Model - Fiati, Rina; Widowati, -; K. N, Dinar Mutiara (JOIV : International Journal on Informatics Visualization, 2025)
Digital technology brings a paradigm shift to the education quality ecosystem. Mobile learning provides an innovative space and motivation for information system users. The purpose of the research is to identify users who are adopting technology and support effective and efficient digital-based learning processes so that they can be improved in the future. It will also support an effective and efficient digital-based learning process, thereby increasing its usefulness in the future. The Technology Acceptance Model employs a method to evaluate technology acceptance based on the behavioral perception of information system users. Completion and data analysis using structural equation modeling validate the system that integrates satisfaction and academic performance values. Research materials were distributed through participant questionnaires targeting Mobile learning users via online forms. The study was conducted through a survey of students distributed through a questionnaire. A total of 510 participants were obtained. Based on a demographic survey, it was found that 54.24% used smartphones. The results showed that satisfaction and user behavior attitudes impact the intention to continue using mobile technology. The ease of the system has a positive impact on improving academic performance. The influencing factors are user satisfaction, continuation intention, and user behavioral attitude. So, it can be concluded that system usability and subjective norms influence the continuation intention of M-learning implementation. Future research implications can expand the variables from the perspective of motivation and economic factors in using mobile to improve online learning.